The Parliamentary Rules of Procedure of the Seventh Grand National Assembly - Mihaylova, Ekaterina (Yearbook of the Law Department, 2022)
The study is devoted to the debates and provisions in the rules of procedure of the Seventh Grand National Assembly. The main controversial issues between the political forces represented in the parliament are indicated – what is a parliamentary group, „for“ and „against“ he adoption of constitutional or organic laws by a qualified majority, the forms of parliamentary control and the demand for political responsibility from the deputies to the government. An analysis is made of what of these parliamentary rules has turned to be actual constitutional provisions.